EFFECTIVENESS OF GROUP COUNSELING SERVICES TO HELP STUDENTS LEARNING DIFFICULTIES - Erlina Harahap (Universitas Muhammadiyah Tapanuli Selatan, 2016)
The study is based on the problem of students still have difficulty in learning, the general problem of this research is